2020
DOI: 10.1016/j.physletb.2019.135172
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of chiral symmetry restoration in dilepton production

Abstract: We study the structural change of the vector spectral function and integrated production rates of dileptons in the presence of the chiral mixing induced exclusively at finite density. The mixing produces multiple bumps and peaks around the vacuum masses of the ρ, ω and φ resonances in the spectral function. The arising modification becomes pronounced when the mass difference between parity partners decreases. In particular, the emergent peaks around the vacuum φ meson in the production rates serves as an excel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…Previous studies have pointed out the importance of the QCD phase transitions, where the additional latent heat can trigger the local production of neutrinos (Klähn & Fischer 2015;Fischer et al 2016Fischer et al , 2018Fischer et al , 2020Klähn et al 2017;Bauswein et al 2019a,b; A82, page 2 of 14 Pereira et al 2020). This also motivates further study and possible applications of the proposed model in the context of HIC at finite temperature, where a novel signature of chiral symmetry restoration within the dense hadronic sector in dilepton production was recently proposed (Sasaki 2020).…”
Section: Introductionmentioning
confidence: 72%
“…Previous studies have pointed out the importance of the QCD phase transitions, where the additional latent heat can trigger the local production of neutrinos (Klähn & Fischer 2015;Fischer et al 2016Fischer et al , 2018Fischer et al , 2020Klähn et al 2017;Bauswein et al 2019a,b; A82, page 2 of 14 Pereira et al 2020). This also motivates further study and possible applications of the proposed model in the context of HIC at finite temperature, where a novel signature of chiral symmetry restoration within the dense hadronic sector in dilepton production was recently proposed (Sasaki 2020).…”
Section: Introductionmentioning
confidence: 72%
“…This is even more pronounced in a class of models with sequential chiral and deconfinement phase transitions, such as the hybrid QMN model. This may have important phenomenological implications for the study of multi-messenger astronomy and heavy ion collisions (HIC) [59].…”
Section: Resultsmentioning
confidence: 99%
“…We note that in reference [26], it was shown that the confinement mechanism of the hybrid QMN model leads to strengthening of the chiral phase transition when compared to pure quark or hadronic models without confinement. This motivates further study and possible applications of the model, not only in the context of multi-messenger astronomy, but also in the context of heavy ion collisions (HIC) at finite temperature and density, where a novel signature of chiral symmetry restoration within the dense hadronic sector in dilepton production was recently proposed [59]. Publisher's Note The EPJ Publishers remain neutral with regard to jurisdictional claims in published maps and institutional affiliations.…”
Section: Discussionmentioning
confidence: 99%
“…[26], it was shown that the confinement mechanism of the hybrid QMN model leads to strengthening of the chiral phase transition when compared to pure quark or hadronic models without confinement. This motivates further study and possible applications of the model, not only in the context of multi-messenger astronomy, but also in the context of heavy ion collisions (HIC) at finite temperature and density, where a novel signature of chiral symmetry restoration within the dense hadronic sector in dilepton production was recently proposed [59].…”
Section: Discussionmentioning
confidence: 99%